Chemopreventive Potential of Calotropis gigantea Root Fraction on MCF-7 Cells: In Vitro and In Silico Study - Rifki Febriansah; Vidia Noviyanti (Indonesian Journal of Cancer Chemoprevention, 2025)
Cancer remains a major global health issue due to its high mortality rate. Chemotherapy, though commonly used, often causes severe side effects by damaging both cancerous and healthy cells. Therefore, safer and more selective chemopreventive agents from natural sources are needed. This study aims to evaluate the chemopreventive potential of the ethanol fraction of biduri root (EFBR, Calotropis gigantea L.) through in vitro and in silico approaches. Phytochemical screening was used to identify bioactive compounds. Molecular docking using AutoDock Vina assessed calotropin’s interaction with Bcl-2 and HER-2 proteins. Antioxidant activity was measured by the DPPH method, and cytotoxic activity was tested on MCF-7 breast cancer cells and normal Vero cells using the MTT assay. EFBR was found to contain cardiac glycosides, flavonoids, terpenoids, saponins, and tannins. Docking results showed strong binding of calotropin to Bcl-2 (-9.3 kcal/mol) and HER-2 (-8.1 kcal/mol). EFBR showed weak antioxidant activity (IC₅₀: 518.93 μg/mL) but moderate cytotoxicity against MCF-7 (IC₅₀: 159.80 μg/mL), with low toxicity on Vero cells (IC₅₀: 2703.61 μg/mL) and a high selectivity index (SI: 16.91). These results indicate that EFBR has potential as a selective chemopreventive agent against breast cancer.Keywords: Calotropis gigantea L., molecular docking, MTT assay, DPPH, MCF-7.